Catalogue de matériel forestier de reproduction 2025-2029. - Centre National de Semences Forestières (CNSF) (2024)
The National Tree Seed Center of Burkina Faso (CNSF) provides stakeholders with Forest Reproductive Materials (FRMs) consisting of seeds, plant parts and seedlings, adapted to the conditions of the Sudano-Sahelian zones and to the needs of users. The publication is a catalogue of a wide range of FRMs that can be supplied to stakeholders involved in reforestation, for use in interventions contributing to the adaptation and mitigation of climate change and to meet the needs of the local rural communities. It is intended to be a reference guide to support stakeholders in better use of quality FRMs. This catalogue is the culmination of years of research by CNSF on the domestication of local plant species. This updated version was developed through a participatory process led by CNSF researchers and involving several experts. In this effort, CNSF partnered with the Alliance of Bioversity International and CIAT and obtained financial support from the CGIAR Initiative NATURE+, which promotes inclusion of local biodiversity in forest landscape restoration in Burkina Faso.